UPAYA PEMERINTAH KOTA DENPASAR DALAM PENANGANAN PELANGGARAN KETENTUAN TENTANG PENCEMARANSAMPAH DI KOTA DENPASAR - Arya Anggana Putra, Agus; Wairocana, I Gusti Ngurah; Sudiarta, I Ketut (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 03, Mei 2014, 2014)
Solid waste is the waste material from household activities , markets , offices , lodging houses , hotels , restaurants, industries , puingan building materials and scrap - iron former motor vehicle . Efforts made by the government in the handling of garbage in violation of the provisions set in the lawNo. 18 of 2008 concerning waste management while Denpasar Government waste problems in regulation set in the area of Denpasar No. 3 of 2000 on hygiene and public order in the city of Denpasar , increasing the number of residents in the city of Denpasar with high growth rates result in increasing the volume of the garbage .This article usine empirical legal . Empirical legal is to conduct research through field observation ,which concluded Lack of community participation in the management of hygiene is not maximized , so it needs to be further enhanced through the implementation of socialization .
Keywords: Handling Garbage violation Conditions About Pollution